Editorial - Sirkeci, Ibrahim (Border Crossing, 2019)
In this issue, the first paper is by Argun Abrek Canbolat and deals with extended consciousness in a literature review. The second contribution is by Philip L. Martin and looks at the Trump administration's migration policies in the US. Carsten Schaefer examines and discusses the Chinese efforts to control and utilise diaspora. The last paper by Peter O’Brien discusses the borders and irregular migration.